The Risks of Rhetoricity: Accounting for Intellectual Disability in the Rhetorical Tradition - Barritt, Anna (My University, 2023)
I am troubled by the notion that what specialists in my field call “rhetoricity”—the quality of being able to assess an audience and effectively influence their thinking—is what separates humans (“rhetors”) from non-humans. This binary is problematic when we account for individuals with intellectual/developmental disabilities (I/DD), whose rhetorical prowess diverges from our accepted models. Recent trends in rhetorical studies, however, have widened how rhetoric defines itself, including expanding not only what rhetoric is and does, but also what entities (ex. animals, objects, sounds) are able to exercise agency. Yet, little scholarship has taken up people with I/DD as sites of rhetorical possibility. My project explores this possibility by examining the intersection of rhetorical theory and profound cognitive impairment. I analyze the generative potential of the past and future of intellectual disability in order to understand not only how rhetoric has influenced the understanding of and treatment of disabled people, but how disability collides with the study of rhetoric. Each chapter of my project excavates how rhetoric shapes the material reality of disability and the ways in which the bodies and minds of people with intellectual disabilities transform our understanding of rhetoric. My findings suggest that embracing profound disability deepens the scope of rhetorical studies and challenges our understanding of rhetoric’s origins, functions, and boundaries. In doing so, I offer a richer, more diverse view of what it means not only to be rhetorical, but to be an active, valued participant in the world.
Keywords: rhetoricity; intellectual disability; rhetorical studies